Robust partial integrated guidance and control approaches for maneuvering targets - Ji, Yi; Lin, Defu; Pei, Pei; Shi, Xingwei; Wang, Wei (International journal of robust and nonlinear control, 2019)
Summary A novel observer‐controller framework algorithm based on barrier Lyapunov function and second‐order sliding mode control is presented, which can drive the first‐ and second‐order states of the typical second‐order dynamics subject to unknowns and uncertainties simultaneously converge to zero in finite time. The obtained results are applied in the designs of two partial integrated guidance and control laws for an aerodynamic control interceptor against maneuvering targets: one is for zeroing line‐of‐sight angular rate and the other is for hit‐to‐kill. Owing to the inherent properties of different bandwidth and time delay between control commands and missile dynamics, partial guidance and control is separated with two loops. The outer loop achieves the target maneuvers and generates the control command, and the inner loop is used to track it. Moreover, to overcome the excessive differentiation problem of conventional backstepping design, two integral Lyapunov functions are introduced, which avoid the differentiation of the virtual control laws. Finally, detailed stability discussion and simulation results of the proposed partial guidance and control approaches demonstrate these properties.